Risk factors for pulmonary arterial hypertension in children and young adults. Issue 5 (1st November 2016) - Naumburg, Estelle; Söderström, Lars; Huber, Daniel; Axelsson, Inge
Summary: Objectives: Pulmonary hypertension (PH) has been linked to preterm birth explained by congenital heart defects and pulmonary diseases. Working hypothesis: Other factors may influence the risk of PH among adolescences and children born premature. Study design: This national registry‐based study assess risk of PH following premature birth adjusted for known risk factors. Patient‐subject selection and methodology: All cases born 1993–2010, identified by diagnostic codes applicable to PH and retrieved from the Swedish Registry of Congenital Heart Disease (N = 67). Six controls were randomly selected and matched to each case by year of birth and hospital by the Swedish Medical Birth Register (N = 402). Maternal and infant data related to preterm birth, pulmonary diseases, and congenital defects were retrieved. The association between preterm birth and pulmonary hypertension was calculated by conditional logistic regression taking into account potential confounding factors. Results: One third of the cases and seven percent of the controls were born preterm in our study. Preterm birth was associated with PH, OR = 8.46 (95%CI 2.97–24.10) ( P < 0.0001) even after adjusting for confounding factors. Other factors, such as acute pulmonary diseases, congenital heart defects, congenital diaphragm herniation, and chromosomal disorders were also associated with PH in the multivariate analysis. Conclusions: Children and young adults born preterm are known to have an increased risk of PH, previously explained by congenital heart defects and pulmonary diseases. By adjusting for such factors, our study indicates that new factors may play a role in the risk of developing PH among children born preterm.Pediatr Pulmonol. 2017;52:636–641. © 2016 Wiley Periodicals, Inc.